Evaluation of damage mechanisms in tight gas reservoirs: Field example from perth Basin - Bahrami, N. (Society of Petroleum Engineers, 2015)
Tight gas reservoirs represent a significant portion of natural gas reservoirs worldwide. Production at economical rates from tight gas reservoirs in general is very challenging not only due to the very low intrinsic permeability but also as a consequence of several different forms of formation damage that can occur during drilling, completion, stimulation, and production operations. Tight gas reservoirs generally do not flow gas to surface at commercial rates, unless the well is completed using advanced technologies and efficiently stimulated. One of the major damage mechanisms in tight gas reservoirs is liquid phase trapping damage that is controlled by pore system geometry, capillary pressure, relative permeability and interfacial tension between the invading trapped fluid and reservoir fluid. The liquid invasion damage into the rock matrix reduces the near wellbore permeability as a result of temporary or permanent trapping of liquid inside the porous media, and results in low productivity in tight gas reservoirs. This study presents evaluation of damage mechanisms in tight gas reservoirs and the methods that can provide improved well productivity by minimizing damage to the formation. Numerical reservoir simulation is integrated with tight gas field data analysis and core flooding experiments to better understand the effect of different damage mechanisms on well productivity in order to propose the possible remedial strategies that can help achieve viable gas production rates from tight gas reservoirs. Copyright 2015, Society of Petroleum Engineers.